Family business employer brand: Understanding applicants' perceptions and their job pursuit intentions with samples from the US and Belgium. Issue 3 (September 2018) - Arijs, Diane; Botero, Isabel C.; Michiels, Anneleen; Molly, Vincent
Abstract: Recruiting college educated non-family employees has been one of the challenges identified by family business owners affecting the success and continuity of family firms. To better understand this challenge, we build on previous work from recruitment, branding, and family business literature to introduce the family business employer brand construct and its components. We explore the perceptions that non-family applicants have about the family business employer brand components, and how these perceptions affect intentions to pursue a job with a family firm. Data were collected through surveys in the USA (N = 293) and Belgium (N = 324). Results from both countries indicate that participants evaluated instrumental (i.e., compensation, job security, and advancement opportunities) and symbolic (i.e. trustworthiness, innovation, thrift, style, and dominance) components of the family business employer brand differently in the two countries and these factors varied in the effect that they had on the intent to pursue a job in a family firm. Implications of these results for practice and further research are discussed.